Prognostic value of quality of life score in disease-free survivors of surgically-treated lung cancer. Issue 1 (December 2016) - Yun, Young; Kim, Young; Sim, Jin; Shin, Ae; Chang, Yoon; Lee, Jongmog; Kim, Moon; Shim, Young; Zo, Jae
Abstract Background We aimed to evaluate the prognostic value of quality of life (QOL) for predicting survival among disease-free survivors of surgically-treated lung cancer after the completion of cancer treatment. Methods We administered the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30), the Quality of Life Questionnaire Lung Cancer Module (QLQ-LC13), Hospital Anxiety and Depression Scale (HADS), and Posttraumatic Growth Inventory (PTGI) to 809 survivors who were surgically-treated for lung cancer at two hospitals from 2001 through 2006. We gathered mortality data by linkage to the National Statistical Office through December 2011. We used Cox proportional hazard models to compute adjusted hazard ratios (aHRs) and 95 % confidence intervals (CIs) to estimate the relationship between QOL and survival. Results Analyses of QOL items adjusted for age, sex, stage, body mass index, and physical activity showed that scores for poor physical functioning, dyspnea, anorexia, diarrhea, cough, personal strength, anxiety, and depression were associated with poor survival. With adjustment for the independent indicators of survival, final multiple proportional hazard regression analyses of QOL show that physical functioning (aHR, 2.39; 95 % CI, 1.13–5.07), dyspnea (aHR, 1.56; 95 % CI, 1.01–2.40), personal strength (aHR, 2.36; 95 % CI, 1.31–4.27), and anxiety (aHR, 2.13; 95 % CI, 1.38–3.30) retained their independent prognostic power of survival. Conclusion This study suggests that patient-reported QOL outcomes in disease-free survivors of surgically-treated lung cancer after the completion of active treatment has independent prognostic value for long-term survival.